Taḥlīl al-Qiyam al-Akhlāqiyah fī Kitāb al-Qirā’ah al-Rasyīdah al-Juz’ al-Ṡānī (Dirāsah al-Adab al-Ijtimā’ī) - Dodi Robiansyah (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2022)
The objectives of this research are to know and explain an ethical message in the book of Qira>aturrasyi>dah, and to know and explain the form of moral values in the book of of Qira>aturrasyi>dah Part II.. The method of qualitative research, with the social approach to literature the data sources used contain basic data including the book of rational reading, journals and related articles and secondary data including dictionary, books and the Internet. The data collection techniques used are library, reading, data analysis and note-taking. The technique of its analysis is descriptive and qualitative. The results of the search from the message to the moral of moral values are honesty, "God does not cost a soul except in its power," and help, love, and care among creatures. The form of moral values in it is harmony, usefulness or help, and please help, care for others, and help each other. After conducting analysis and discussion, several conclusions can be drawn that are that every human being must possess honesty regardless of his social status. Everything we sow we will reap, and God has created His creatures according to their quotas, and God does not cost a soul except its power, and help all things, even if they are small.